Comparative Effectiveness of Cognitive Behavioral Therapy 5 Sessions and 12 Sessions Toward to Post Traumatic Stress Disorder on Post Flood Disaster Adolescent - Uray Fretty Hayati; Sari Fatimah; Ai Mardhiyah (Faculty of Nursing Universitas Padjadjaran, 2018)
AbstractFlood disaster conduced 2375 refugees and traumatic in adolescent with symptoms of Post Traumatic Stress Disorder as many as 15 people in Garut regency. The impact of PTSD on adolescents reduced brain volume, behavioral changed and short-term memory lost. The psychotherapy that proved to be effective overcome PTSD was Cognitive Behavioral Therapy (CBT) 12 sessions but the empirical evidence in Indonesia, the 12 session of CBT intervention was too long, tedious, and caused doubts to the therapist so that 5 session CBT intervention was considered more flexible and efficient. The purpose of this study was compare the effectiveness of PTSD scores pre and post intervention of CBT 5 sessions and 12 sessions toward of PTSD on post flood disaster in adolescent. This research used Quasi Experiment Design with Pre test and Post test approach Two Group Design. The first group was given CBT 5 sessions and the second group was given CBT 12 sessions with the total number of adolescent respondents were 38 people (aged 12–18). The sample was chosen by used Consecutive Sampling at two evacuation sites in Cilawu and Tarogong Kidul subdistrict, Garut regency, West Java, Indonesia. The results of this study pre and post intervention in both groups decreased of PTSD score which difference of median value of 6.00 on CBT 5 session and average difference of 7.58 on CBT 12 session with significancy (p-value < 0.01) and the result analysis test on the effectiveness of both interventions (p-value > 0.05) with significancy number 0.648. The conclusion was no significant difference between the effectiveness of the CBT group of 5 sessions and the CBT group of 12 sessions. There needs comparison of more than 5 sessions and less than 12 sessions for next research.